Effectiveness of Educational Supervision in Sultanate of Oman as Perceived by Teachers - Rashid S. Al Fahdi; Helis M. Al Oriami; Rashid S. Al Mehrzi; Naser H. Al Rasbi (Sultan Qaboos University, 2013)
The study aimed at identifying the effectiveness of educational supervision in public schools in the Sultanate of Oman. To achieve the aim of the study, a questionnaire was designed. It consisted of 49 items distributed into five domains. The domains are: enhancement of instructional and learning processes; school's activities and media; implementation, assessment, and development of curriculum; assessment of instructional and learning process; and teachers' professional development. The validity and reliability of the questionnaire were examined. The sample of the study consisted of 592 male and female teachers. The results showed that educational supervision in Oman had high effectiveness on enhancement of instructional and learning processes, school's activities and media, whereas, it had medium effectiveness on the other three domains. Based on the results, few recommendations have been suggested.